Impacto do Role Play na mudança de percepção do estudante de Medicina sobre habilidades de comunicação demonstradas em vídeo de consulta ortopédica - RODRIGUES, T. V. (2018)
The change in the perception of the medical student about communication skills demonstrated in a orthopedic appointment video was evaluated after intervention using Role Play and expository class. Methodology: Experimental study in medical education, in which compared the perception of students of the 4th year of the UNIFENAS medical school, Alfenas Campus, about the use of communication skills when watching the film of a clinical care in orthopedics, before and after intervention. The students were divided into two groups. The two groups watched an orthopedic appointment video and recorded their perceptions related to communication skills in a semi-structured instrument. Then , the Control Group had an expositive class and the Test Group developed a Role Play session, both about communication skills. One week later, both groups watched the same video and perfomed a new register about their perceptions related to communication skills, in an equal instrument to the previous one. The perception of each student was evaluated through records made before and after intervention. Results: The Test Groups (n = 15) and Control Groups (n = 18) were matched according to age, sex, and academic perfomance in medicine course , to avoid bias in the study. The results did not show statistically significant differences as to the intervention, both intragroup and intergroup, although several scientific evidences point to the relevance of the Role Play technique in the training of communication skills. Conclusion: Both Role Play and expository class did not influence significantly students' perceptions about communication skills demonstrated in orthopedic appointment video. Possible study limitations: 1. Insufficient sample size to show effect of intervention; 2. The video of the appointment explained very clear the inability of the doctor's communication; 3. The fact that the expository class has happened to only 18 students may have favored the interaction between teacher and student and may have hampered the difference of the result between the two interventions; 4. The time of one week between the phases may have allowed the exchange of information between the groups.